Chromosomal replication origin from the marine bacterium Vibrio harveyi functions in Escherichia coli: oriC consensus sequence. - Zyskind, J W (1983)
The chromosomal replication origin (oriC) of Vibrio harveyi has been isolated on a plasmid and shown to function as an origin in Escherichia coli. The nucleotide sequence of the V. harveyi oriC was determined. From a comparison of this sequence with oriC sequences of five enteric bacteria, we derived a consensus sequence of bacterial origins that function in E. coli. This consensus sequence identifies 122 positions within oriC where nucleotide substitutions can occur without loss of origin function. These positions are clustered rather than scattered. Four interrelated nine-base-pair repeats and eight of the dam methylation G-A-T-C sites are conserved in the consensus sequence. Very few relative insertion-deletion changes occur, and these are localized to one region of oriC. The genes for three polypeptides linked to the V. harveyi oriC were identified by using in vitro protein synthesis directed by deletion derivative plasmid templates. One of these genes, coding for a 58,000 Mr polypeptide and located 3.0 kilobase pairs from the V. harveyi oriC region, is lethal to E. coli when many copies (approximately 40 per cell) are present (high copy lethal or HCL gene). In addition, nucleotide sequence analysis showed that a different gene, the gid gene to the left of oriC, is highly conserved between E. coli and V. harveyi, whereas the coding region to the right of oriC is much less conserved.